Análisis de la preocupación ambiental y su relación con el bienestar juvenil en el contexto de la urbanización de jóvenes de comunidades rurales de Bolivia - Guillén Aguirre, Natalie (2025)
This study examines the relationship between environmental concern and well-being among adolescents in rural communities, recognizing that these perceptions influence urbanization processes in Bolivia. The research was based on surveys administered to 639 adolescents, aged 12 to 18, across four rural communities, using validated instruments such as the Environmental Concern Scale and the Satisfaction with Life Scale. The findings show a positive association between well-being and a stronger emotional connection with nature. In contrast, attitudes such as environmental apathy or an exclusively human-centered (anthropocentric) perspective tend to be linked to lower levels of well-being. These results highlight the need to address issues such as eco-anxiety and to create opportunities for young people to engage in environmental initiatives within their own territories. In this context, it is essential to promote educational programs and public policies that strengthen the connection between youth and their environment. Such measures could help reduce migration to urban areas, reinforce a sense of belonging, and encourage sustainable practices that support youth well-being and the long-term sustainability of their communities.